Hubungan antara Usia dan IMT dengan Kejadian Hipotermi Post Spinal Anestesi - Muhammad Hafiduddin; Aprillia Amesabila Br.Tarigan; Pradita Ayu Fernanda (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Background: Spinal anesthesia is a procedure that involves administering drugs through the lumbar interspinous gap into the subarachnoid space. Hypothermia, a condition in which the body's core temperature drops below 36°C, carries a higher risk in the elderly and can cause serious perioperative complications. Body Mass Index (BMI) is an important parameter used to assess nutritional status, closely related to obesity and body fat mass, and can influence the body's response to anesthesia. Objective: This study aims to identify the relationship between hypothermia and age and BMI in post-spinal anesthesia patients at RSI Muhammadiyah Tegal. Method: This observational research with a cross-sectional design involved 73 samples selected through purposive sampling, with data analyzed using the Spearman Rank test to test the correlation between variables. Results: Most respondents were aged 19-44 (60.3%) and female (71.2%). As many as 58.9% of respondents experienced mild hypothermia, and 49,3% had normal BMI (18.5-25.5). The Spearman Rank test results showed a significant relationship between hypothermia and age and BMI after spinal anesthesia (p=0.008, P<0.05). Conclusion: There is a substantial association between hypothermia and age and BMI post-spinal anesthesia, indicating the importance of monitoring these factors perioperatively to reduce the risk of possible complications